Identification of SNPs and Candidate Genes for Milk Production Ability in Yorkshire Pigs - Shi, Lijun; Li, Yang; Liu, Qian; Zhang, Longchao; Wang, Ligang; Liu, Xin; Gao, Hongmei; Hou, Xinhua; Zhao, Fuping; Yan, Hua; Wang, Lixian (Frontiers in Genetics, 2021)
Sow milk produce ability is an important limiting factor impacting suboptimal growth and survival of piglets. By pig genetic improvement, the litter size has been increased, and larger litters need more suckled mammary glands, that results in increased milk from lactating sow. Hence, it has much significance to explore the sow lactation performance. For the milk produce ability, it is not practical to directly measure the milk yield, we used litter weight gain (LWG) throughout sow lactation as an indicator. In this study, we estimated the heritability of LWG, namely, 0.18 ± 0.07. Further, we performed a GWAS, and detected seven significant SNPs, namely, Sus scrofa Chromosome (SSC) 2: ASGA0010040 (P = 7.73E-11); SSC2:MARC0029355 (P = 1.30E-08), SSC6: WU_10.2_6_65751151 (P = 1.32E-10), SSC7: MARC0058875 (P = 4.99E-09), SSC10: WU_10.2_10_49571394 (P = 6.79E-08), SSC11: M1GA0014659 (P = 1.19E-07), and SSC15: MARC0042106 (P = 1.16E-07). We performed the distribution of phenotypes corresponding to genotypes of seven significant SNPs, and showed that ASGA0010040, MARC0029355, MARC0058875, WU_10.2_10_49571394, M1GA0014659, and MARC0042106 had extreme phenotypic values corresponded to the homozygous genotypes, while the intermediate values corresponded to the heterozygous genotypes. We screened for flanking regions ± 200 kb nearby the seven significant SNPs, and totally identified 38 genes. Among of them, 28 as the candidates were involved in lactose metabolism, colostrum immunity, milk protein, and milk fat by functional enrichment analysis. Through the combined analysis between 28 candidate genes and transcriptome data of sow mammary gland, we found nine commons (ANO3, MUC15, DISP3, FBXO6, CLCN6, HLA-DRA, SLA-DRB1, SLA-DQB1, and SLA-DQA1). Further, by comparing the chromosome positions of the candidate genes with the quantitative trait locus (QTLs) previously reported, a total of 17 genes were found to be within 0.86 Mb to 94.02 Mb of the reported QTLs for sow milk produce ability, in which, NAV2 was found to be located with 0.86 Mb of the QTL region ssc2: 40936355. In conclusion, we identified seven significant SNPs located on SSC2, 6, 7, 10, 11, and 15, and proposed 28 candidate genes for milk produce ability in Yorkshire pigs. Among of them, 10 were the key candidates.